UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN SOSIOLOGI MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS X.4 SMA N 1 LEMBAH MELINTANG - Ilmi Ilmi (STKIP Pesisir Selatan, 2017)
Based on the results of student learning X.4SMA Class N 1 Valley Crossing in the subjects of Sociology found that results for students in the subjects of Sociology is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in subjects Sociology sub Describing the occurrence of deviant behavior and anti-social attitudes through Learning Model Cooperative Integrated Reading and Composition (CIRC) in Class X.4 SMA N 1 Transverse Valley District Pasaman Barat.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 42 students Grades X.4 SMA N 1 Valley Crossing. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Learning Model Cooperative Integrated Reading and Composition (CIRC) can improve student learning outcomes in subjects Sociology sub Describing the occurrence of deviant behavior and anti sosialdi SMA N 1 Valley Crossing. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 49.36 (Not Good) increased to 83.69 (Good) with an increase of 34.33%.